On the equivalence of some perturbations of the operator of multiplication by the independent variable - Linchuk, Yu. S.; Лінчук, Ю. С. (Institute of Mathematics, NAS of Ukraine, 2016)
We study the conditions of equivalence of two operators obtained as perturbations of the operator of multiplication by the independent variable by certain Volterra operators in the space of functions analytic in an arbitrary domain of the complex plane starlike with respect to the origin.